2016
DOI: 10.4103/0259-1162.172343
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane in low-flow anesthesia using “equilibration point”

Abstract: Context:While giving low-flow anesthesia, it is a routine practice to give fixed duration of initial high-flow. This study was conducted to show the use of equilibration point as changeover point from initial high-flow to low-flow.Aims:It was to compare the use of equilibration point, hemodynamics, end-tidal agent concentration, recovery time, and recovery score between isoflurane and sevoflurane.Settings and Design:It was a prospective randomized study conducted on 100 patients who were admitted for elective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“… 23 , 24 Many studies have shown that low-flow anesthesia is similar to or better than high-flow anesthesia in terms of recovery times. 10 , 25 In the present study, rescue times were similar in both groups, consistent with the findings of other studies.…”
Section: Discussionsupporting
confidence: 93%
“… 23 , 24 Many studies have shown that low-flow anesthesia is similar to or better than high-flow anesthesia in terms of recovery times. 10 , 25 In the present study, rescue times were similar in both groups, consistent with the findings of other studies.…”
Section: Discussionsupporting
confidence: 93%
“…We used sevoflurane as an inhaled anesthetic agent. In their study, McGain et al [9] and Chatrath et al [10] suggested switching from desflurane to sevoflurane to minimize the cost and environmental impact of inhalation anesthesia, based on the high cost, low potency, and greater greenhouse gas effect of desflurane.…”
Section: Discussionmentioning
confidence: 99%
“…have documented mean equilibration time of 8 min for sevoflurane, which is much more than what we recorded (4.59 ± 0.77 min). [5] They used 2.6% concentration of sevoflurane for all patients while we used age-specific MAC value that may have shortened the equilibration time in some cases reducing the average. In the earlier studies, Thepakorn et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the earlier studies, Thepakorn et al . have used 1:1:12 wash in the scheme of desflurane using 1 L O 2 and N 2 O each and 12% desflurane[25] that yielded a shorter wash-in period for desflurane. However, it caused tachycardia and hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation